Maternal Factors Associated with Fine Motor Skills Development in Toddlers with Stunting - Shinta Utami; Nuur Octascriptiriani Rosdianto; Ranti Lestari (Jurnal Ragam Pengabdian, 2026)
Early childhood is a golden age, where nutrition supports growth and development, including fine motor skills. This development can also be influenced by the mother's education, occupation, household income, and parenting style. This study aims to identify factors associated with the development of fine motor skills in toddlers experiencing stunting. This is a correlational study with a cross-sectional approach. The sample consisted of 59 mothers with stunted toddlers using total sampling. Data collection was conducted using the Parental Feeding Style Questionnaire and KPSP. Statistical analysis was performed using Chi-Square Analysis. The results of the Chi-Square test showed that there was a relationship between the mother's education (p=0.000), occupation (p=0.000), household income income (p=0.000), and parenting style (p=0.000) with the fine motor development of toddlers. The conclusion shows that there is a relationship between maternal education, maternal employment, household income, and parenting style with the fine motor development of toddlers.